Seroprevalence of human herpesvirus 8 in Ireland among blood donors, men who have sex with men, and heterosexual genitourinary medicine and infectious diseases clinic attendees. Issue 8 (9th March 2021) - O'Rourke, Sadhbh; O'Flaherty, Niamh; Coyne, Dermot; Lynam, Almida; Clarke, Susan; O'Dea, Siobhán; Fitzpatrick, Sarah; Connell, Jeff; Crowley, Brendan
Abstract: Human herpesvirus 8 (HHV‐8) seroprevalence varies geographically and between subpopulations. High seroprevalence rates have been ascribed to men who have sex with men (MSM), African migrants, and HIV‐infected individuals. The objective of this study was to determine the seroprevalence of HHV‐8 in an Irish population, including specific risk groups. A cross‐sectional study of 200 blood donors and 200 genitourinary medicine (GUM) and infectious diseases (ID) clinic patients was performed, with testing for Immunoglobulin G (IgG) antibodies to HHV‐8 lytic antigens using a commercial indirect fluorescence assay (Scimedx Corp.). Verification was performed at the Centers for Disease Control and Prevention (CDC). All 200 blood donor samples were negative for HHV‐8 IgG antibodies. 21% of GUM and ID patients were positive for HHV‐8 IgG antibodies. One hundred of these patients were MSM, 35% of whom were HHV‐8 seropositive (46% of HIV‐positive MSM and 24% of HIV‐negative MSM). Of 100 heterosexual patients, only 7% were HHV‐8 seropositive. The absence of seropositivity in 200 Irish blood donors may suggest that Ireland has a low overall population HHV‐8 seroprevalence. The proportion of HHV‐8 seropositivity in the MSM population was significantly higher than in the heterosexual population and most marked in HIV‐positive MSM.